The Moderating Effect of Higher Education on Intergenerational Spatial Inequality - Elise de Vuijst; Maarten van Ham; Reinout Kleinhans (Institute for the Study of Labor (IZA), 2015)
It is well-known that socioeconomic outcomes and (dis)advantage over the life course can be transmitted from parent to child. It is increasingly suggested that these intergenerational effects also have a spatial dimension, although empirical research into this topic remains scarce. Previous research from Sweden and the United States shows that children who grow up in disadvantaged neighbourhoods experience long-term exposure to such neighbourhoods in their adult lives. This study contributes to the literature by examining to what extent educational attainment can break the link between parental neighbourhood disadvantage and the neighbourhood experiences of children as adults up to 12 years after leaving the parental home. We use longitudinal register data from the Netherlands to study a complete cohort of parental home leavers, covering 119,167 individuals who were followed from 1999 to 2012. Using sequence analyses as a visualisation method, and multilevel logit models, we demonstrate that children who lived in deprived neighbourhoods with their parents are more likely to live in similar neighbourhoods later in life than children who grew up in more affluent neighbourhoods. We find that intergenerational neighbourhood patterns of disadvantage can be discontinued when individuals attain higher education over time. Discontinuation is however less prevalent among individuals from ethnic minority groups.
Keywords: I30; J60; P46; R23; 330; intergenerational inequality; neighbourhood effects; deprived neighbourhoods; neighbourhood histories; educational attainment; longitudinal data; sequence analysis; the Netherlands